alarm
Ask a question for free
Math
Modiswyn

If P(x) = x3 + 2x2 + 9x + 10, find P(-2) – P(0) + P(2)

answers: 1
Register to add an answer
Answer:

P(x)=x³+2x²+9x+10.

P(-2)=(-2)³+2(-2)²+9(-2)+10.

=-8+2(4)-18+10. (Because +×-=-).

=-8+8-18+10.

=0-18+10. (Because -×+=- so, -8+8 will cancel i.e., it will be zero(0)).

=-18+10.

=-8. (Because -×+=- & largest number is important).

P(0)=(0)³+2(0)²+9(0)+10.

=0+2(0)+0+10.

=0+0+0+10.

=10.

P(2)=(2)³+2(2)²+9(2)+10.

=8+2(4)+18+10.

=8+8+18+10.

=16+18+10.

=34+10.

=44.

P(-2)-P(0)+P(2)=-8-10+44.

=-18+44. (Because -×-=+ & largest number is important).

=26. (Because -×+=- & largest number is important).

I think this is your answer.

377
Sherry
For answers need to register.
Contacts
mail@expertinstudy.com
Feedback
Expert in study
About us
For new users
For new experts
Terms and Conditions